The culture of Japan as seen through its leisure - Linhart, Sepp; Frühstück, Sabine (SUNY series in Japan in transition., 1998)
The Culture of Japan as Seen through Its Leisure brings together scholars of various disciplines from around the globe to discuss different forms of leisure activities in past and present Japan, thus enriching our knowledge of Japanese culture. Arranged in five sections, the volume focuses on everyday activities such as leisure, sports, travel and nature, theater and music, playing games, and gambling. The editors place the treated leisure activities into a historical frame of reference and relate them to the well-known classification scheme of games by Roger Caillois.